Food Analysis - Nielsen, S. Suzanne (Springer, 2019)
The intent of this fifth edition book is the same as that described in the Preface to the first four editions – a text primarily for undergraduate students majoring in food science, currently studying the analysis of foods. However, comments from users of the first four editions have convinced me that the book is also a valuable text for persons in the food industry who either do food analysis or interact with analysts. The big focus of this edition was to do a general update on methods and to make the content easier for readers to compare and contrast methods covered. The following summarize changes from the fourth edition: (1) general updates, including addition and deletion of methods, (2) three new chapters (“Determination of Total Phenolics and Antioxidants Capacity in Food and Ingredients,” “Food Microstructure Techniques,” “Food Forensic Investigation”), (3) rewrote and/or reorganized some chapters, (4) added tables to some chapters to summarize and compare methods, and (5) added some colored figures. As stated for the first four editions, the chapters in this textbook are not intended as detailed references, but as general introductions to the topics and the techniques. Course instructors may wish to provide more details on a particular topic to students. Chapters focus on principles and applications of techniques. Procedures given are meant to help explain the principles and give some examples, but are not meant to be presented in the detail adequate to actually conduct a specific analysis. As in the first four editions, all chapters have summaries and study questions, and keywords or phrases are in bold type, to help students focus their studies. The grouping of chapters by category is similar to the fourth edition. However, due to the increased use of spectroscopy and chromatography for many basic analyses, chapters on these topics are covered early in the book. Instructors are encouraged to cover the topics from this text in whatever order is most suitable for their course. Also, instructors are invited to contact me for access to a website I maintain with additional teaching materials related to this textbook and the accompanying laboratory manual.